Progressive Muscle Relaxation Terhadap Kadar Glukosa Darah Diabetes Melitus Tipe 2 Terkontrol dan Tidak Terkontrol - Wahyudi, Dian Arif; Arlita, Indah (Universitas Aisyah Pringsewu (UAP) Lampung, 2019)
The main problem people with type 2 DM is uncontrolled blood glucose levels, if the condition continuously occur will cause microvascular and macrovascular complications. The main key to preventing complications and maintaining the helath condition of type 2 DM is control blood glucose levels. One of the interventions that can be done with physical activity and relaxation there is PMR.This study is Quasi experiment two group pre-posttest design .The sample size of 26 respondents divided into two groups 13 Type 2 DM with normal glucose levels (controlled) and 13 Type 2 DM was hyperglycemic glucose (uncontrolled) based on 2 hour fasting. Both groups were given PMR intervention and deep breath relaxation techniques for 30 minutes. The study used a paired t test α less than 0.05.The results the mean blood glucose levels in the controlled Type 2 DM group was 133.69 mg/dl ± 30,546, paired t test ρ 0,001 (less than 0.05) and the uncontrolled Type 2 DM group averages 271.54 mg/dl ± 60,363, paired t test ρ 0.001 (less than 0.05). Based on the above test Ho is rejected, meaning there is any effects of PMR with blood glucose level both of them controlled Type 2 DM groups and uncontrolled type 2 DM.PMR intervention able to reduce blood glucose levels in patients with Type 2 DM with normal or hyperglycemic conditions, so that people with Type 2 DM to reduce blood glucose levels not only with drug treatment or diet but also can apply physical activity and relaxation like PMR training.